ANALISIS PENILAIAN KINERJA PADA PT PERKEBUNAN NUSANTARA 1 REGIONAL 5 KEBUN TEMBAKAU AJONG JEMBER - umi farhatin farhatin; Nafisatun Nawroh; Ria Riski Pusiyah; Fahri Dina Maulana; Aprilya Fitriani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the employee performance appraisal system at PT Tembakau Ajong and the factors influencing its effectiveness. The study was conducted to understand how the performance evaluation process is implemented to improve work quality, discipline, and employee productivity at the company. The research method used was descriptive qualitative, with data collection techniques through interviews, observation, and documentation. Informants in this study consisted of management and several company employees directly involved in the performance appraisal process. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. Data obtained from interviews and observations were then analyzed to determine the form of performance appraisal implemented and its impact on employee performance. The results indicate that the performance appraisal system at PT Tembakau Ajong is conducted periodically, taking into account aspects of work discipline, responsibility, attendance, work quality, and the ability to work collaboratively among employees. Performance appraisals have a positive impact on increasing employee motivation and productivity due to the evaluation and feedback provided by the company. Factors influencing performance appraisals include employee discipline, communication between superiors and subordinates, the work environment, work motivation, and the company's reward system. With a good performance appraisal system, companies can improve work effectiveness and achieve organizational goals more optimally